2019
DOI: 10.18178/ijtef.2019.10.4.642
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic-Word-of Mouth on e-Loyalty and Consumers’ e-Purchase Decision Making Process: A Social Media Perspective

Abstract: The idea behind the concept of Electronic Wordof-Mouth (e-WOM) is important to the visibility of individuals and businesses on social media. Although the e-WOM is increasingly adopting in Vietnam, the association of e-WOM with social media among Vietnamese is an under-researched area.Accordingly, drawing on Social Cognitive Theory, this study aims to identify the role of e-WOM in developing e-loyalty and thus e-purchase. This study develops a model consisting of e-WOM as an independent variable, e-loyalty, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 56 publications
2
12
0
1
Order By: Relevance
“…e-WOM proved to have a significant positive affect on e-loyalty with a T-statistic value of 4.171 > 1.645 and a standardized coefficient of 0.282. This result is in line with prior research by Perera et al (2019), and (Khan & Azam, 2016) on the impact of e-loyalty on social media perspective. However, what is interesting from the respondent's profile is that there are as many as 63% of respondents who do not follow Sayurbox's social media accounts.…”
Section: Figure 1 Outer Research Framework Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…e-WOM proved to have a significant positive affect on e-loyalty with a T-statistic value of 4.171 > 1.645 and a standardized coefficient of 0.282. This result is in line with prior research by Perera et al (2019), and (Khan & Azam, 2016) on the impact of e-loyalty on social media perspective. However, what is interesting from the respondent's profile is that there are as many as 63% of respondents who do not follow Sayurbox's social media accounts.…”
Section: Figure 1 Outer Research Framework Modelsupporting
confidence: 92%
“…In the research by Rita et al (2019), there are several factors which affect the e-service quality on e-loyalty, such as application design, customer service and fulfillment. While e-recovery is greatly influenced by responsiveness, compensation and contact (Shafiee & Bazargan, 2018), in addition to research modifications from Perera et al (2019) it was found that e-WOM can also determine the e-loyalty which leads to increase online repurchase intention and generate long-term benefits. This prior research was taken because it has similiar relevance to online purchases with current research.…”
Section: Introductionmentioning
confidence: 99%
“…E-wom pada penelitian ini dapat diukur dalam tiga dimensi yaitu, kepedulian terhadap orang lain (concern for others), mengekspresikan perasaan positif atau negatif (expressing positive feelings), membantu perusahaan (helping the company). Terdapat beberapa penelitian sebelumnya yang menujukkan keterkaitan e-wom dengan keputusan pembelian online, sebagaimana penelitian yang dilakukan oleh Yunitasari (2018); Oktaviani (2020); Sindunata & Wahyudi (2018); Perera, et al (2019); Tjhin & Aini (2019), Bahwa e-wom berpengaruh positif terhadap keputusan pembelian online. Berdasarkan hasil studi tersebut maka dapat disusun hipotesis kedua:…”
Section: Pendahuluanunclassified
“…Another study showed that people do not always adopt online word of mouth, even from credible websites, because people know that now a days, anybody can sign up and make an account on the website to post a comment. Hence, not every buzz created on these websites attracted people, and this buzz did not affect people's purchasing decisions (Perera, Nayak & Long, 2019).…”
Section: Hypothesismentioning
confidence: 99%